Mengatasi Tantangan Manajemen Kelas Inklusif melalui Strategi Pengajaran Guru di SMP Smart Auladi Cirebon - Fuadah, Fuadah (Journal of Educational Integration and Development (JEID), 2025)
Inclusive education has become a national program in Indonesia, but its implementation still faces various challenges, especially among teachers who need support to provide optimal services for students with special needs. This research aims to explore inclusive classroom management strategies at Smart Auladi Cirebon Middle School to support the development of students according to their individual potential, conditions and characteristics. A descriptive qualitative approach was used by collecting data through in-depth interviews, observation and documentation studies. Data analysis was carried out thematically to identify challenges, strategies and solutions for implementing inclusive classroom management. The research results show that the main challenges include teachers' limited understanding of inclusive concepts, less effective classroom management, and a lack of supporting resources. The strategies implemented include teacher training, collaboration with parents, and the use of individual approaches in teaching. This research recommends the development of sustainable training programs, the provision of adequate resources, and the implementation of integrated, inclusive classroom management guidelines. It is hoped that these findings can become a reference for similar schools in improving the quality of inclusive education in a sustainable manner.   Keywords: Inclusive Classroom Management, Inclusive Teaching Strategies, Challenges of Inclusive Education   ABSTRAK Pendidikan inklusif telah menjadi program nasional di Indonesia, namun implementasinya masih menghadapi berbagai tantangan, terutama di kalangan guru yang membutuhkan dukungan untuk memberikan layanan optimal bagi peserta didik berkebutuhan khusus. Penelitian ini bertujuan mengeksplorasi strategi manajemen kelas inklusif di SMP Smart Auladi Cirebon guna mendukung perkembangan peserta didik sesuai potensi, kondisi, dan karakteristik masing-masing. Pendekatan kualitatif deskriptif digunakan dengan pengumpulan data melalui wawancara mendalam, observasi, dan studi dokumentasi. Analisis data dilakukan secara tematik untuk mengidentifikasi tantangan, strategi, dan solusi implementasi manajemen kelas inklusif. Hasil penelitian menunjukkan tantangan utama meliputi keterbatasan pemahaman guru terhadap konsep inklusif, manajemen kelas yang kurang efektif, dan kurangnya sumber daya pendukung. Strategi yang diterapkan mencakup pelatihan guru, kolaborasi dengan orang tua, serta penggunaan pendekatan individual dalam pengajaran. Penelitian ini merekomendasikan pengembangan program pelatihan berkelanjutan, penyediaan sumber daya yang memadai, dan penerapan panduan manajemen kelas inklusif yang terintegrasi. Temuan ini diharapkan dapat menjadi acuan bagi sekolah serupa dalam meningkatkan kualitas pendidikan inklusif secara berkelanjutan.